Interactions of glial cells with neuronal synapses, from astrocytes to microglia and oligodendrocyte lineage cells. Issue 6 (17th February 2023) - Liu, Yao; Shen, Xi; Zhang, Yuhan; Zheng, Xiaoli; Cepeda, Carlos; Wang, Yao; Duan, Shumin; Tong, Xiaoping
Abstract: The mammalian brain is a complex organ comprising neurons, glia, and more than 1 × 10 14 synapses. Neurons are a heterogeneous group of electrically active cells, which form the framework of the complex circuitry of the brain. However, glial cells, which are primarily divided into astrocytes, microglia, oligodendrocytes (OLs), and oligodendrocyte precursor cells (OPCs), constitute approximately half of all neural cells in the mammalian central nervous system (CNS) and mainly provide nutrition and tropic support to neurons in the brain. In the last two decades, the concept of "tripartite synapses" has drawn great attention, which emphasizes that astrocytes are an integral part of the synapse and regulate neuronal activity in a feedback manner after receiving neuronal signals. Since then, synaptic modulation by glial cells has been extensively studied and substantially revised. In this review, we summarize the latest significant findings on how glial cells, in particular, microglia and OL lineage cells, impact and remodel the structure and function of synapses in the brain. Our review highlights the cellular and molecular aspects of neuron‐glia crosstalk and provides additional information on how aberrant synaptic communication between neurons and glia may contribute to neural pathologies. Main Points: Astrocytes, microglia, and oligodendrocyte lineage cells remodel the structure and function of synapses in the brain. Aberrant synaptic communications between neurons and glia contribute to neural pathologies.